Win to Exit Perma-Death and Resurrection in Sword Art Online and Log Horizon - McConeghy, David (2018)
Trapped inside their virtual-reality gaming worlds, players in both Sword Art Online and Log Horizon find themselves fighting virtual battles for their real-world lives. This essay looks at the secular approaches to issues of death and dying presented by these Japanese anime television series. Instead of relying on Buddhism or Shintoism, the characters in these shows use gaming mechanics to explain their predicament. Eternal life becomes a source of ennui in Log Horizon where players are trapped and resurrected upon death. In Sword Art Online, players find new value in their virtual lives, but fear perma-death in both worlds at the hands of players who continue to see the game as solely a game. Video games and anime are powerful tableaus for exploring death and religion, but they are used here to greatest effect to show that social contracts between players do not end when their virtual lives begin.
Keywords: death and dying; Log Horizon; religion and popular culture; Secularism; Sword Art Online; Video Games; Virtual Reality; gamevironments